2007
DOI: 10.1002/jbm.a.31767
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and pellet suspension culture promote differentiation of human mesenchymal stem cells into insulin producing cells

Abstract: Multipotential mesenchymal stem cells (MSCs) isolated from bone marrow can differentiate into multiple mesenchymal tissues and exhibit a neuronal phenotype under appropriate induction conditions. Methods promoting neural differentiation have been adapted to derive insulin producing cells (IPCs) from embryonic stem cells, but it remains unclear whether neuronal cell-based differentiation method will be able to derive IPCs from MSCs. Using a four-stage differentiation protocol which contains neuronal differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Gao et al (2008) have indicated that extracellular matrix gel plays an important role not only in differentiation of human umbilical cord blood derived MSCs into IPCs, but also in maturation and formation of three dimensional structures. This observations were confirmed by other authors (Chang et al 2008). …”
Section: Differentiation Of Other Types Of Mscssupporting
confidence: 91%
“…Gao et al (2008) have indicated that extracellular matrix gel plays an important role not only in differentiation of human umbilical cord blood derived MSCs into IPCs, but also in maturation and formation of three dimensional structures. This observations were confirmed by other authors (Chang et al 2008). …”
Section: Differentiation Of Other Types Of Mscssupporting
confidence: 91%
“…Cells in cell clusters, affected by surrounding cells via paracrine, easily coordinated each other and differentiated. Chang and colleagues showed that human BMSCs centrifuged into cell pellets more easily differentiated towards IPCs than those under a monolayer [8]. Studies have shown that cell–cell contact between pancreatic beta-cells is important for maintaining their survival and increasing insulin secretion [24].…”
Section: Discussionmentioning
confidence: 99%
“…Their directed differentiation and subsequent transplantation has met only with partial success in preclinical models (66)(67)(68)(69)(70)(71)(72)(73)(74)(75). However, when directly infused in an undifferentiated state onto diabetic subjects, a variable degree of endogenous regeneration has been observed (76)(77)(78)(79). It is now broadly believed that MSCs are at their therapeutic best when used in this context, probably due to their wellstudied immunomodulatory, anti-inflammatory, proangiogenic, and trophic properties (80)(81)(82)(83)(84)(85)(86)(87).…”
Section: Adult Stem Cellsmentioning
confidence: 99%